Adipose tissue‐derived extracellular matrix hydrogels as a release platform for secreted paracrine factors - Dongen, Joris A.; Getova, Vasilena; Brouwer, Linda A.; Liguori, Gabriel R.; Sharma, Prashant K.; Stevens, Hieronymus P.; Lei, Berend; Harmsen, Martin C. (Journal of tissue engineering and regenerative medicine, 2019)
Fat grafting is an established clinical intervention to promote tissue repair. The role of the fat's extracellular matrix (ECM) in regeneration is largely neglected. We investigated in vitro the use of human adipose tissue‐derived ECM hydrogels as release platform for factors secreted by adipose‐derived stromal cells (ASCs). Lipoaspirates from nondiabetic and diabetic donors were decellularized. Finely powdered acellular ECM was evaluated for cell remainders and DNA content. Acellular ECM was digested, and hydrogels were formed at 37°C and their viscoelastic relaxation properties investigated. Release of ASC‐released factors from hydrogels was immune assessed, and bio‐activity was determined by fibroblast proliferation and migration and endothelial angiogenesis. Acellular ECM contained no detectable cell remainders and negligible DNA contents. Viscoelastic relaxation measurements yielded no data for diabetic‐derived hydrogels due to gel instability. Hydrogels released several ASC‐released factors concurrently in a sustained fashion. Functionally, released factors stimulated fibroblast proliferation and migration as well as angiogenesis. No difference between nondiabetic and diabetic hydrogels in release of factors was measured. Adipose ECM hydrogels incubated with released factors by ASC are a promising new therapeutic modality to promote several important wound healing‐related processes by releasing factors in a controlled way.